2015
DOI: 10.1007/s00125-015-3621-9
|View full text |Cite
|
Sign up to set email alerts
|

OGTT and random plasma glucose in the prediction of type 1 diabetes and time to diagnosis

Abstract: Aims/hypothesis We assessed the utility of the OGTT and random plasma glucose concentrations in predicting the time to diagnosis of type 1 diabetes. Methods A population-derived cohort of 14,876 newborns with HLA-conferred risk of type 1 diabetes were invited to regular follow-up for islet autoantibodies. When two or more autoantibodies were detected, an OGTT was performed once a year and random plasma glucose analysed twice a year. During follow-up, 567 children developed multiple autoantibodies, 255 (45%) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 29 publications
2
56
0
Order By: Relevance
“…Study inclusion was solely based on positivity to multiple autoantibodies, without considering genetic risk. HLA‐genotype was however determined after inclusion, and the distribution of genotypes associated to low, medium, or high risk of T1D showed that few individuals were classified as having high risk ( n = 4), while the vast majority had moderate ( n = 8) or low ( n = 9) risk (Table ). To increase the number of individuals in each subgroup and enable comparison between progressors and non‐progressors, we also grouped the children into those with increased risk (HLA‐genotypes conferring moderate or high risk) or without increased risk (low HLA‐risk genotypes).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Study inclusion was solely based on positivity to multiple autoantibodies, without considering genetic risk. HLA‐genotype was however determined after inclusion, and the distribution of genotypes associated to low, medium, or high risk of T1D showed that few individuals were classified as having high risk ( n = 4), while the vast majority had moderate ( n = 8) or low ( n = 9) risk (Table ). To increase the number of individuals in each subgroup and enable comparison between progressors and non‐progressors, we also grouped the children into those with increased risk (HLA‐genotypes conferring moderate or high risk) or without increased risk (low HLA‐risk genotypes).…”
Section: Resultsmentioning
confidence: 99%
“…Although dysglycemia was seen in many of the progressors long before disease onset, disturbed glycemic control was in fact observed in the majority of participants (14/21) without any significant difference between progressors and non‐progressors. The possibilities to predict diabetes and estimate time of disease onset based on measures of dysglycemia in high‐risk individuals have been addressed by previous studies . In the DIPP study, dysglycemia detected by random plasma glucose or during OGTT was a useful marker of progression to diabetes .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FPIR is constantly higher in non‐progressors than in progressors. Adapted from the original data from refs Koskinen et al , Helminen et al , Sosenko et al .…”
Section: Preclinical Stage Of Type 1 Diabetes In Childrenmentioning
confidence: 99%
“…In a series of 403 DIPP children with multiple islet autoantibodies impaired fasting glucose (IFG) and impaired glucose tolerance (IGT) in an OGTT as defined by WHO were predictive for T1D with a HR of 3.2 and 8.3, respectively. The median time to diagnosis after IGT was 0.7 years showing that the simple 2‐point OGTT may also provide important information when estimating the time to clinical diagnosis of T1D .…”
Section: Oral Glucose Tolerance Test (Ogtt)mentioning
confidence: 99%